UMPSAs electric buses and vans make campus debut - T.N., Alagesh (New Straits Times Press (M) Bhd., 2023)
PEKAN: Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has rolled out its first electric buses and vans at its campuses here.